Media Sosial sebagai Pengganti Institusi Tradisional dalam Pembentukan Norma Sosial - Amaani, Fauziyyah; Al-Ghifary, Muhammad Firdhi; Amelia, Nanda; Azizah, Sarah Nur; Hufad, Achmad; Achdiani, Yani (Labor Program Studi Pendidikan Sosiologi, 2025)
Social media has transformed the social dynamics of modern society replacing the role of traditional institutions in shaping social norms Institutions such as family school and religion previously the main pillars in constructing social values are now being displaced by the influence of digital media This study aims to analyze how social media functions as a new institution in the formation of social norms using the perspective of Talcott Parsons Structural Functionalism Theory particularly the AGIL framework Adaptation Goal Attainment Integration and Latency A qualitative method was employed involving teenage participants aged 17 20 who are actively engaged with social media The findings show that social media not only facilitates communication but also establishes new standards in social behavior moral values and political engagement Therefore social media has emerged as a new institution that defines social norms replacing the role of traditional institutions in society < p>